Burst-suppression is reactive to photic stimulation in comatose children with acquired brain injury. Issue 8 (August 2016) - Nita, Dragos A.; Moldovan, Mihai; Sharma, Roy; Avramescu, Sinziana; Otsubo, Hiroshi; Hahn, Cecil D.
Highlights: In comatose children, the EEG burst ratio increases during photic stimulation. Burst ratio reactivity, the degree of change in the burst ratio during photic stimulation, correlates with the Glasgow Coma Scale score. Burst ratio reactivity may represent a simple tool to monitor coma severity in critically ill children. Abstract: Objective: Burst-suppression is an electroencephalographic pattern observed during coma. In individuals without known brain pathologies undergoing deep general anesthesia, somatosensory stimulation transiently increases the occurrence of bursts. We investigated the reactivity of burst-suppression in children with acquired brain injury. Methods: Intensive care unit electroencephalographic monitoring recordings containing burst-suppression were obtained from 5 comatose children with acquired brain injury of various etiologies. Intermittent photic stimulation was performed at 1 Hz for 1 min to assess reactivity. We quantified reactivity by measuring the change in the burst ratio (fraction of time in burst) following photic stimulation. Results: Photic stimulation evoked bursts in all patients, resulting in a transient increase in the burst ratio, while the mean heart rate remained unchanged. The regression slope of the change in burst ratio, referred to as the standardized burst ratio reactivity, correlated with subjects' Glasgow Coma Scale scores. Conclusions: Reactivity of the burst-suppression pattern to photic stimulation occurs across diverse coma etiologies. Standardized burst ratio reactivity appears to reflect coma severity. Significance: Measurement of burst ratio reactivity could represent a simple method to monitor coma severity in critically ill children.